Childrearing, motherhood and fatherhood in Ghana - Nyarko, K. (Parenting Across Cultures, 2014)
This study examines childrearing practices, motherhood, and fatherhood in Ghana. It looks at the contextual background of the country, ethnic groupings, family systems and childrearing practices, and the patrilineal and matrilineal systems. The evidence shows that mothers are oriented towards the permissive style of parenting, whereas fathers use an authoritarian style. However, it further shows that some mothers and fathers use an authoritative parenting style. The study also revealed that some parents accept corporal punishment as a method of disciplining children, while others frowned on its usage. The study underscores the importance of situating parenting within one’s culture.
Keywords: Parenting Style; Family System; Corporal Punishment; Physical Punishment; Ethnic Grouping